Undergraduate business and environmental science students' recycling behavior at an Appalachian University - Pauko, Andras (2014)
The purpose of this study was to investigate what the students know about and how they relate (attitudes) to recycling, what influence (subjective norms) them to recycle or not to recycle and what recycling related challenges (perceived behavioral control) they face in a university setting compared to their home environment. Eight students participated in the study. Four of them were majoring in an environmental science related major, and the other four were business major students. The three main variables of Ajzen’s (1991) Theory of Planned Behavior, attitudes, subjective norms and perceived behavioral control, were used to examine the participants recycling behaviors. The data was collected through individual interviews. The results revealed that all of the participants had access to information on recycling, their attitudes were positive toward recycling and they found recycling challenging and inconvenient on campus because of the lack of recycling culture at the university. Adequate information and positive attitude were somewhat helpful in motivating the participants to recycle on campus. However, subjective norms and most importantly perceive behavioral controls had the largest impact on the participants’ recycling behavior, the last one being the most significant variable. Comparing recycling behavior at home and on campus strengthened the role of subjective norms and perceived behavioral control in influencing recycling behavior among the participants.